2020
DOI: 10.1109/access.2020.2993562
|View full text |Cite
|
Sign up to set email alerts
|

Neural Networks-Based Aerodynamic Data Modeling: A Comprehensive Review

Abstract: This paper reviews studies on neural networks in aerodynamic data modeling. In this paper, we analyze the shortcomings of computational fluid dynamics (CFD) and traditional reduced-order models (ROMs). Subsequently, the history and fundamental methodologies of neural networks are introduced. Furthermore, we classify the neural networks based studies in aerodynamic data modeling and illustrate comparisons among them. These studies demonstrate that neural networks are effective approaches to aerodynamic data mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 116 publications
(114 reference statements)
0
28
0
Order By: Relevance
“…In the modeling of aerodynamic data from wind tunnel tests on a variety of aircraft, a utilization of the neural network method occurred [19]. In [20,21], a rectangular wing with the NACA0015 profile, pitching from α = 0 • to α = 60 about the 1/4 chord location • , is introduced using the ANN model.…”
Section: Neural Network Modelmentioning
confidence: 99%
“…In the modeling of aerodynamic data from wind tunnel tests on a variety of aircraft, a utilization of the neural network method occurred [19]. In [20,21], a rectangular wing with the NACA0015 profile, pitching from α = 0 • to α = 60 about the 1/4 chord location • , is introduced using the ANN model.…”
Section: Neural Network Modelmentioning
confidence: 99%
“…Furthermore, neural networks have also been widely employed in several scientific and technological fields. Among the research studies found in the literature it is worth mentioning the application of neural networks for prediction of biogases concentration using spiking neural networks [45], feature recognition and process planning of casting dies [46], quality control in manufacturing processes [47], prediction of springback in sheet metal forming [48], aerodynamic data modeling [49], detection of skin diseases [50], automatic control of house elements [51,52] and energy forecasting in the manufacturing sector [53], among many other applications.…”
Section: State Of the Artmentioning
confidence: 99%
“…The geometry shape of airfoils greatly affects the aerodynamic performance, the parameterization as well as the aircraft inverse design [1,2]. One of a traditional airfoil design method is to define airfoil geometry parameters manually, which is effective to perceive the variations in airfoil geometry structures [3].…”
Section: Introductionmentioning
confidence: 99%